2010
DOI: 10.1007/s11926-010-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Scleroderma

Abstract: The importance of the genetic component in the pathogenesis of scleroderma, or systemic sclerosis, has been strengthened in the past 2 years with studies on genetic markers-either candidate gene or genome-wide association studies--in large case-control series. Multiple genes have been consistently associated with susceptibility to scleroderma, and interestingly, several of them are involved in immune regulation. Because many of these genes are shared with other autoimmune diseases, a common underlying autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…SSc is a complex disease, where no single polymorphism is known to cause the complete manifestation of the condition; it has been suggested that it may be the combined action of several single nucleotide polymorphisms in different genes that may result in the complex traits of the disease. 7 We compared patients with SSc with a control population and demonstrated that oral problems in patients with SSc include decreased oral opening, decreased saliva production, increased number of missing teeth, and worse periodontal disease. [8][9][10] The radiographic manifestations in the jaws, considered characteristic of SSc, are welldefined bony erosions at the sites of muscle attachment in the mandible and increasing width of periodontal ligaments around teeth.…”
mentioning
confidence: 99%
“…SSc is a complex disease, where no single polymorphism is known to cause the complete manifestation of the condition; it has been suggested that it may be the combined action of several single nucleotide polymorphisms in different genes that may result in the complex traits of the disease. 7 We compared patients with SSc with a control population and demonstrated that oral problems in patients with SSc include decreased oral opening, decreased saliva production, increased number of missing teeth, and worse periodontal disease. [8][9][10] The radiographic manifestations in the jaws, considered characteristic of SSc, are welldefined bony erosions at the sites of muscle attachment in the mandible and increasing width of periodontal ligaments around teeth.…”
mentioning
confidence: 99%
“…6 The fact that the IL2RA rs11594656 minor allele shows a protective effect in both SLE 6 and SSc (the current study) should also be noted, because these diseases have a very similar genetic component and most of their shared associations are in the same direction. 9,10 Moreover, low circulating levels of soluble IL2RA have been found to be associated with the IL2RA Table 2 Pooled analysis of the allelic combinations of the IL2RA genomic region accordingly with the global disease (SSc), the limited subtype (lcSSc) and ACA production Allelic combination Controls, Abbreviations: ACA, anti-centromere auto-antibodies; CI, confidence interval; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For example, most of the genetic associations of systemic sclerosis (SSc) are shared with SLE. 9,10 SSc, also called scleroderma, is a chronic multisystem disease of unknown aetiology, characterised by fibrotic events, vasculopathy and production of auto-antibodies against nuclear self-antigens, including anti-centromere auto-antibodies (ACAs) and anti-topoisomerase antibodies (ATA). 11 Two main clinical subsets of the disease have been described based on the extent of skin involvement: limited cutaneous scleroderma (lcSSc) and diffuse cutaneous scleroderma (dcSSc).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on genetic susceptibility suggest that HLA/MHC-associated loci and other non-associated loci are involved in the pathogenesis of SSc (20) . The HLA-associated gene NOTCH4 has been linked to both SSc-specific antibodies: antitopoisomerase-I antibody (ATA) and anti-centromere antibody (ACA).…”
Section: Overview Of Systemic Sclerosismentioning
confidence: 99%